The Effect of Profitability, Liquidity, Leverage, and BI 7 Days Repo Rate on Dividend Payout Ratio in Telecommunication Companies Listed on the Indonesia Sharia Stock Index (ISSI) 2021-2023 - Shauqi Aditya Khalis; Muhammad Ikhsan Harahap; Atika Atika (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2024)
The aim of this study is to analyze the effect of profitability, liquidity, leverage, and the BI 7 Days Repo Rate on dividend payouts in Indonesia. The research focuses on four telecommunication companies listed on the Indonesia Sharia Stock Index (ISSI) for the period 2021-2023. The method employed is balanced panel data with a common effect model. The results of the study reveal that debt to equity (leverage) has a significant impact on the dividend payout ratio, while profitability, liquidity, and the BI 7 Days Repo Rate do not significantly influence the dividend payout ratio. This study highlights the importance of leverage in dividend policy for telecommunication companies. Reducing leverage can increase dividend payments, benefiting shareholders. Investors may use lower leverage as an indicator of higher potential dividends. From the perspective of Islamic economic law, companies listed on the Sharia Stock Index are expected to adhere to principles of ethical finance, ensuring transparency and justice in wealth distribution, including dividend payouts. In line with Maqasid al-Shariah, maintaining balanced financial structures that reduce excessive debt is crucial to promoting equitable wealth sharing among stakeholders. Future research should consider expanding the sample, exploring other sectors, extending the time period, and including additional factors such as return on assets, quick ratio, and tax rate.